Is CT Still Useful in the Study Protocol of Retinoblastoma? - Galluzzi, P.; Hadjistilianou, T.; Cerase, A.; De Francesco, S.; Toti, P.; Venturi, C. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Intralesional calcium deposition is considered a key element for differentiating retinoblastoma from simulating lesions. Our aim was to assess whether MR imaging associated with ophthalmologic investigations (ophthalmoscopy and ultrasonography) could replace CT in the detection of diagnostic intralesional calcifications in retinoblastoma. MATERIALS AND METHODS: Ophthalmoscopic findings, MR images, CT scans, and histologic examination of 28 retinoblastomas from 23 consecutive children (11 males, 12 females; age range at admission, 1–35 months; mean age, 11 months; median age, 9 months) were retrospectively evaluated. Ultrasonography was performed in 18 patients with 21 retinoblastomas. MR imaging included T2-weighted spin-echo and gradient-echo images, fluid-attenuated inversion recovery images, and T1-weighted spin-echo images with and without contrast enhancement. Clinical data were integrated with MR imaging data to evaluate the utility of both approaches to discover calcifications; particularly, a correlation between intralesional signal-intensity void spots on MR imaging and hyperattenuating areas on CT scans was performed. RESULTS: Ophthalmoscopy detected calcifications in 12 of 28 eyes (42.85%). Ultrasonography detected calcifications in 20 of 21 eyes (95.23%). CT showed hyperattenuating intralesional areas consistent with calcifications in 27 of 28 eyes (96.42%). MR imaging showed intralesional signal-intensity void spots in 25 of 28 eyes (89.28%). All spots detected with MR imaging matched the presence of calcifications on CT scans. Gradient-echo T2*-weighted and fast spin-echo T2-weighted images showed the highest degree of correlation with CT. When we put together ophthalmoscopy, ultrasonography, and MR imaging data, no calcifications detected on CT were missed, and the differential diagnosis was thorough. CONCLUSIONS: A combination of clinical data and MR images may remove potentially harmful ionizing radiation from the study protocol of retinoblastoma.